2011
DOI: 10.1073/pnas.1101684108
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression profile of the antiviral restriction factor and tumor-targeting antigen CD317/BST-2/HM1.24/tetherin in humans

Abstract: Human CD317 is an intrinsic immunity factor that restricts the release of enveloped viruses, including the major pathogens HIV and Lassa virus, from infected cells in culture. Its importance for infection control in humans is unclear, due in part to its incompletely defined in vivo expression pattern. CD317 also has been proposed as a selective target for immunotherapy of multiple myeloma. To provide a framework for studies of the biological functions, regulation, and therapeutic potential of CD317, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 46 publications
7
95
1
Order By: Relevance
“…2). These data are consistent with recent reports that showed that monocytes displayed approximately 10 times more BST-2 molecules on a per-cell basis than T lymphocytes in healthy subjects (25,33), but they contrast with results of a recent study that did not detect basal BST-2 expression in leukocyte subsets (16). No significant upregulation was observed after treatment with inducers of NF-B (TNF-␣ and PMA) or NF-AT (ionomycin) pathways, even after different induction times (3 to 48 h) and increasing doses ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…2). These data are consistent with recent reports that showed that monocytes displayed approximately 10 times more BST-2 molecules on a per-cell basis than T lymphocytes in healthy subjects (25,33), but they contrast with results of a recent study that did not detect basal BST-2 expression in leukocyte subsets (16). No significant upregulation was observed after treatment with inducers of NF-B (TNF-␣ and PMA) or NF-AT (ionomycin) pathways, even after different induction times (3 to 48 h) and increasing doses ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…As such, these viruses are likely to frequently encounter tetherin (28,29), and their replication is consequently inhibited. Indeed, this appears to be the situation for LP-BM5, whose replication and pathogenesis are attenuated by tetherin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During viral infection, tetherins on the cell surface and viral envelope can prevent virion release either by direct cross-linking or by the formation of dimers between adjacent coiled-coil domains (20). Tetherin is constitutively expressed in mature B cells, some cancer cell lines, bone marrow stromal cells, monocyte-derived macrophages, and plasmacytoid dendritic cells, and its expression can be induced by type I and II interferon (IFN) treatment (21)(22)(23)(24)(25)(26)(27)(28). Thus, tetherin may play a fundamental role in the initiation and perpetuation of a virus-specific immune response.…”
mentioning
confidence: 99%